Аntifungal activity of 5-(2-nitrovinyl) imidazoles and their derivatives against the causative agents of vulvovaginal candidiasis - N. D. Yakovychuk; S. Y. Deyneka; A. M. Grozav; A. V. Humenna; V. B. Popovych; V. S. Djuiriak (Regulatory Mechanisms in Biosystems, 2018)
Development of resistance of yeast-like fungi belonging to the Candida genus to the existing antifungal medicines as well as the high toxicity and low tolerance of these medicines in many cases stipulate the acute need for new antibiotic compounds. In this context, an extremely promising group of chemical substances is imidazole derivatives. Therefore, the search for more active and less toxic medical preparations based on imidazole is a relevant and important issue for medical practice. Considering the urgent demand for new antifungal preparations, four new nitro containing imidazole derivatives were synthesized – 5-(2-nitrovinyl) imidazoles and their derivatives. Then in vitro by means of double serial dilution in Saburo liquid nutritious medium we examined their antifungal action against eight clinical strains of yeast-like fungi belonging to the Candida genus: C. albicans, C. guillermondii, C. krusei, С. glabrata, C. kefyr, C. tropicalis, C. inconspicua and C. zeylanoides). They were isolated and identified from the vulvovaginal content of women suffering from vulvovaginal candidiasis. 3-methyl-4-[1-(1-naphthyl-4-chloro-1Н-imidazole-5-yl)-2-nitroethyl-]-1H-pyrazole-5-ole and 2,4-dichloro-5-(2-nitrovinyl)-1-(4-fluorophenyl)-1Н-imidazole were found to be the most active compounds – mean values of minimal fungistatic concentrations of these compounds against all the eight examined strains were 34.9 and 39.7 µg/mL (with the ranges of these concentrations 5.2–83.3 µg/mL) respectively. 2,4-dichloro-3-methyl-4-{2-nitroethyl-1-[1-(4-fluorophenyl)-1Н-imidazole-5-yl]}-1H-pyrazole-5-ole and 1-naphthyl-5-(2-nitrovinyl)-4-chloro-1Н-imidazole were found to possess lower anti-Candida activity – mean values of their minimal fungistatic concentrations against all the eight clinical strains were 48.8 and 51.4 µg/mL (with the ranges of these concentrations 10.4–166.7 µg/mL) respectively. The highest antifungal activity of 5-(2-nitrovinyl) imidazoles and their derivatives was found to be against the clinical strains C. krusei, C. kefyr and C. inconspicua – mean values of minimal fungistatic concentrations concerning the indicated strains were 11.7–26.0 µg/mL. The examined nitro containing imidazole derivatives were found to manifest a slightly lower anti-Candida action against the clinical strains C. tropicalis and C. guilliermondii (mean values of minimal fungistatic concentrations 31.3 and 36.5 µg/mL). The lowest antifungal activity of the examined compounds was detected against the clinical strains C. аlbicans and С. glabrata – mean values of minimal fungistatic concentrations against these strains were 85.9 and 79.4 µg/mL. Comparison of anti-Candida activity of different 5-(2-nitrovinyl) imidazoles and their derivatives enabled us to select their most promising representatives and give recommendations for further synthesis of new nitro containing imidazole derivatives with pronounced antifungal properties.